ANALISIS PENERAPAN DISIPLIN APARATUR SIPIL NEGARA DILINGKUNGAN SEKRETARIAT DAERAH KABUPATEN BENGKULU TENGAH - Rona Pirtha Raflesia; Budiman Sakti; Alexsander Alexsander (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
The Regional Secretariat (Setda) of Central Bengkulu Regency is one of the regional apparatus that functions as a center for administrative and strategic coordination in the implementation of government at the district level. As an organization, every member of the organization, both at the highest and lowest levels, must have discipline in carrying out their duties. As a member of the organization in the Regional Secretariat, of course, it is the State Civil Apparatus (ASN) who works in the Regional Secretariat itself. ASN discipline is not only in carrying out obligations but of course also discipline against the prohibitions that have been determined. If the obligations and prohibitions are violated, then ASN who commits violations should receive disciplinary sanctions, in accordance with the State Civil Service Agency Regulation Number 6 of 2022 concerning the Implementation Regulation of Government Regulation Number 94 of 2021. Without the discipline of ASN within the Regional Secretariat, it is difficult for the Regional Secretariat to achieve good performance. Therefore, this research is focused on ASN discipline on obligations and prohibitions as well as disciplinary sanctions. This research is a qualitative descriptive research, with the method of utanma data collection is interviews with informants. The information used is 6 people. The results of the research conducted show that not all obligations and prohibitions have been implemented by ASN within the Regional Secretariat of Central Bengkulu Regency consistently. Especially in the aspect of the obligation to come to work every working day, to go to work on time and to return to work after the time and the prohibition of leaving the workplace during working hours. ASN who violate discipline are given disciplinary sanctions in accordance with State Civil Service Agency Regulation Number 6 of 2022 concerning Implementation Regulations of Government Regulation Number 94 of 2021. The decision-makers at the Regional Secretariat of Central Bengkulu Regency are advised to improve the discipline of ASN in their environment and provide disciplinary sanctions against ASN who do not comply with obligations and prohibitions by not distinguishing between one ASN and another.  Keywords: Discipline on obligations, discipline on prohibitions and disciplinary sanctions.